N-version programming as an opportunity to exclude errors in software - Cespedes Garcia, P.D. (Математичні машини і системи, 2019)
One of the methods for increasing computer system dependability level is the N-version programming method. Liming Chen and Algirdas Avizienis proposed this concept with the main hypothesis that «independent efforts in software development will significantly reduce the likelihood of identical failures that occurs in two or more versions of the program». The main goal of N-version programming is to increase the reliability of the software by bounding design errors. The effectiveness of a multiversion system depends on the variety of variations at the executive teams formation stage, different algorithms implementation, design and testing tools.